Patterns of Raised Blood Pressure in Vietnam: Findings from the WHO STEPS Survey 2015 - Van Minh Hoang; Quoc Bao Tran; Thi Hoang Lan Vu; Thi Kim Ngan Nguyen; Bao Giang Kim; Quynh Nga Pham; Tuan Lam Nguyen; Duc Truong Lai; Jun Nakagawa; Hai-Rim Shin; Warrick Junsuk Kim; Leanne Riley; et al. (International Journal of Hypertension)
This study aims to describe the prevalence of raised blood pressure and the situation of management for raised blood pressure among the adult population in Vietnam. It also aims to examine the association between diversified socioeconomic and behavioral factors of raised blood pressure and awareness of raised blood pressure. Data were obtained from the STEPS survey conducted in Vietnam in 2015. Survey sample was nationally representative with a total of 3,856 people aged 18–69 years old. The study outcomes included raised blood pressure and awareness of and control of raised blood pressure. Multiple logistic regression was used to examine the association of socioeconomic and behavior risk factors with the outcome variables. The overall prevalence of raised blood pressure in Vietnam in 2015 was 18.9% (95% CI: 17.4%–20.6%). The prevalence of raised blood pressure was higher among men. Significantly correlated factors with raised blood pressure were age, sex, body mass index, and diabetes status. Levels of awareness of raised blood pressure were higher among the older age group and overweight people and lower among ethnic minority groups. Raised blood pressure in Vietnam is a serious problem due to its magnitude and the unacceptably high unawareness rate in the population. Public health actions dealing with the problems of raised blood pressure are urgent, while taking into account its relationship with sex and socioeconomic status. It is clear that the interventions should address all people in society, with a focus on disadvantaged groups which are the rural and ethnic minority peoples.